Adiponectin receptor 1 resists the decline of serum osteocalcin and GPRC6A expression in ovariectomized mice. - Yuan-Yu Lin; Ching-Yi Chen; Shih-Torng Ding (PLoS ONE, 2017)
Hormonal changes that cause metabolic complications are a common problem in postmenopausal women. Adiponectin and osteocalcin are cytokines associated with glucose regulatory and insulin sensitized function in postmenopausal stages. The current study investigated the role of adiponectin signaling and osteocalcin mediated function in glucose metabolism in ovariectomized mice. In a mouse menopausal-related metabolic disorder model, overexpression of adiponectin receptor 1 improved glucose tolerance and caused resistance to body weight increase and decline of serum osteocalcin. Furthermore, adiponectin receptor 1 transgenic ovariectomized mice had higher GPRC6A (the putative osteocalcin receptor) expression in muscle tissue. Immunofluorescence indicated that GPRC6A and adiponectin receptor 1 were co-localized in mouse muscle tissues. The present finding suggested adiponectin receptor 1 can mediate the improvement of glucose metabolism by osteocalcin in ovariectomized mice. Our findings imply the possibility to ameliorate menopause-induced metabolic disorder by GPRC6A and adiponectin signaling.